2023
DOI: 10.1038/s41401-023-01073-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and in vitro pharmacological rescue of KCNQ2 pore mutations associated with epileptic encephalopathy

Abstract: Mutations in the KCNQ2 gene encoding KV7.2 subunit that mediates neuronal M-current cause a severe form of developmental and epileptic encephalopathy (DEE). Electrophysiological evaluation of KCNQ2 mutations has been proved clinically useful in improving outcome prediction and choosing rational anti-seizure medications (ASMs). In this study we described the clinical characteristics, electrophysiological phenotypes and the in vitro response to KCNQ openers of five KCNQ2 pore mutations (V250A, N258Y, H260P, A265… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Results showed that levetiracetam reduced TMS-related spectral perturbation (TRSP) power, lamotrigine increased alpha power and reduced theta band power, while XEN1101 lowered the TRSP power. EEG analysis provides valuable insight into anti-epileptic drug effects 8 .…”
mentioning
confidence: 99%
“…Results showed that levetiracetam reduced TMS-related spectral perturbation (TRSP) power, lamotrigine increased alpha power and reduced theta band power, while XEN1101 lowered the TRSP power. EEG analysis provides valuable insight into anti-epileptic drug effects 8 .…”
mentioning
confidence: 99%